Pengaruh Program Konseling Keperawatan terhadap Self Efficacy pada Ibu Hamil dalam Menghadapi Persalinan Diruang Poliklinik Rumah Sakit Islam Sultan Hadlirin Jepara - Novita Dwi Afriani; Ratna Ratna; Feri Catur Yuliani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Background: Pregnancy is a crucial period that demands the mother's physical and psychological readiness to face childbirth.self efficacyIn pregnant women, it can increase anxiety, fear, and unpreparedness for childbirth, which can impact the health of both mother and fetus. WHO data shows that psychological factors, including low self-confidence, contribute to high rates of childbirth complications in developing countries. Effective interventions are essential to help pregnant women increase self-confidence, manage anxiety, and prepare for childbirth. Nursing counseling is a crucial tool in providing information, emotional support, and building self-confidence in pregnant women.Objective: To find out the influence of nursing counseling programs onself efficacyPregnant women facing childbirth in the polyclinic room of RSI Sultan Hadlirin Jepara. Method: This study used a quasi-experimental pretest-posttest design without a control group. The sample consisted of 62 pregnant women in their final trimester selected using purposive sampling. The intervention consisted of three nursing counseling sessions. The research instrument used a self-efficacy questionnaire, with paired sample t-test data analysis.Results: There is an improvement self efficacywith an average score difference of 1.79 ± 1.05. The t-test showed a calculated t-value of 9.017 with a p-value of 0.000 (p < 0.05), which means there is a significant effect.Conclusion: Nursing counseling programs have been proven to be effective in increasing the self-efficacy of pregnant women, so it is recommended to be a routine part of promotive and preventive efforts in preparing for childbirth. The positive impact of nursing counseling on self-efficacy highlights the importance of integrating psychological support into prenatal care. As the results of this study show, even a few targeted counseling sessions can make a significant difference in a woman’s readiness for childbirth.